2-Phenitidine derivatives as suitable inhibitors of butyrylcholinesterase - Muhammad Athar Abbasi; Aziz-; Muhammad Zahid Qureshi; Farhan Mehmood Khan; Khalid Mohmmed Khan; Muhammad Ashraf; Iftikhar Afzal (Universidade de São Paulo, 2013)
This manuscript reports the synthesis of a series of N-substituted derivatives of 2-phenitidine. First, the reaction of 2-phenitidine (1) with benzene sulfonyl chloride (2) yielded N-(2-ethoxyphenyl) benzenesulfonamide (3), which further on treatment with sodium hydride and alkyl halides (4a-g) furnished into new sulfonamides (5a-g). Second, the phenitidine reacted with benzoyl chloride (6) and acetyl chloride (8) to yield the reported N-benzoyl phenitidine (7) and N-acetyl phenitidine (9), respectively. These derivatives were characterized by infrared spectroscopy, ¹H-NMR, and EI-MS, and then screened against acetylcholinesterase, butylcholinesterase, and lipoxygenase enzyme, and were found to be potent inhibitors of butyrylcholinesterase alone. Este trabalho apresenta a síntese de uma série de derivados da 2-fenetidina N-substituídos. Primeiro, a reação da 2-fenetidina (1) com cloreto de benzenossulfonila (2) conduziu à N-(2-etoxifenil)benzenossulfonamida (3) que, após tratamento com hidreto de sódio e haletos de alquila (4a-g), originou novas sulfonamidas (5a-g). Em segundo lugar, a reação da fenetidina com cloreto de benzoíla (6) e cloreto de acetila (8) conduziu, respectivamente, à N-benzoilfenetidina (7) e N-acetilfenetidina (9). A caracterização destes derivados fez-se por IV, ¹H-RMN e EM-IE. Procedeu-se à avaliação da atividade inibidora destes compostos em relação às enzimas acetilcolinesterase, butirilcolinesterase e lipoxigenase. No entanto, apenas revelaram atividade inibidora da butirilcolinesterase.